Effects of Self–Management Support Program on Preterm Birth Protection Behavior and Preterm Birth among Pregnant Women with High Risk for Preterm Birth - Kiewvijit, Geerawat; Siriarunrat, Supit; Sangin, Siriwan (Journal of The Royal Thai Army Nurses, 2025)
This Quasi-experimental research aimed to investigate the effects of a self-management support program on preterm birth protection behaviors and the rate of preterm birth among pregnant women at high risk for preterm birth. The sample group consisted of 60 pregnant women with a high risk for preterm birth who attended the antenatal care clinic at Ratchaburi Hospital from July to October 2023. The participants were selected based on inclusion criteria and decided in 2 groups, that of an experimental group, and a control group, with 30 women in each group. The experimental group received a self-management support program developed from the self-management support, while the control group received standard nursing care. Data were collected by the personal information questionnaire, the preterm birth protection behaviors questionnaire, and the preterm birth rate recording form, and analyzed using the Independent t-test, and the Dependent t-test statistics. Results found that after participating in the self-management support program, the experimental group had significantly increased the mean score of preterm birth protection behaviors (mean = 19.6, SD = 1.59; t = 21.35, df = 29, p < .001), and this mean score was significantly higher than the control group (mean = 137.07, SD = 10.23; mean = 119.53, SD = 8.70; t = 7.03, df = 58, p < .001). However, the risk of preterm birth in the experimental group was not statistical significantly lower than that of the control group (OR = 0.48; 95% CI = 0.04, 5.63)